Efficacy of Biological and Chemical Control Agents Against the Potato Psyllid (Bactericera cockerelli Šulc) Under Field Conditions - Cárdenass Huaman, Gabriela; Morocho Romero, Henry Hoseph; Casas Niño, Sebastian; Vilchez Navarro, Sandy Graciela; Velarde Apaza, Leslie Diana; Ramirez Rojas, Max; Cruz Luis, Juancarlos Alejandro; Lozano Isla, Flavio; Morocho Romero, Henry (MDPI (Multidisciplinary Digital Publishing Institute), 2025)
Potato (Solanum tuberosum L.) is the third most important food crop worldwide and a cornerstone of food security across the Andean region. However, its production is increasingly threatened by the potato psyllid Bactericera cockerelli (Šulc), the vector of Candidatus Liberibacter solanacearum, the causal agent of the purple-top complex associated with zebra chip disease, which severely reduces both tuber yield and quality. This study was conducted from September 2024 to February 2025 in the province of Huancabamba, Peru, to evaluate the efficacy of biological and chemical control agents against B. cockerelli under field conditions. A randomized complete block design was implemented with five treatments and four replicates, totaling 20 experimental units, each consisting of 20 potato plants (S. tuberosum L.), of which 10 plants were evaluated. Treatments included an untreated control (T0), a chemical control (thiamethoxam + lambda-cyhalothrin, abamectin, and imidacloprid) (T1), and three biological control agents: Beauveria bassiana CCB LE-265 (>1.5 × 10¹⁰ conidia g⁻¹) (T2), Paecilomyces lilacinus strain 251 (1.0 × 10¹⁰ conidia g⁻¹) (T3), and Metarhizium anisopliae (1.0 × 10¹⁰ conidia g⁻¹) (T4). Foliar applications targeted eggs, nymphs, and adults of the psyllid. Results indicated that B. cockerelli mortality across developmental stages was lower under biological treatments compared with T1, which achieved the lowest probability of purple-top symptom expression (46%) and a zebra chip incidence of 60.60%. Among the biological agents, M. anisopliae (T4) reduced incidence to 56.60%, while P. lilacinus (T3) demonstrated consistent suppression of nymphal populations. In terms of yield, T1 achieved the highest tuber weight (198.86 g plant⁻¹) and number of tubers (7.74 plant⁻¹), followed by T3 (5.08) and T4 (4.24). Nevertheless, all treatments exhibited low yields and small tuber sizes, likely due to unfavorable environmental conditions and the presence of the invasive pest. Overall, chemical control was more effective than biological agents; however, the latter showed considerable potential for integration into sustainable pest management programs. Importantly, vector suppression alone does not guarantee the absence of purple-top complex symptoms or zebra chip disease in potato tubers.